High-speed devices and circuits with THz applications - Choi, Jung Han (Boca Raton : Taylor & Francis, CRC Press, 2015)
'This book tries to provide readers with the outlook for the future RF technology by presenting the state-of-the-art results in both new device development and circuit implementations. The book discusses key issues for the circuit operation beyond 100 GHz with respect to device physics, circuit implementations, signal generation, and some technological bottlenecks for system implementations. It presents implementation results using SiGe technologies alternative to CMOS devices'--
'Since the establishment of the Maxwell equation and the discovery of the electromagnetic wave, researchers have been devoted to develop a lot of technologies based on the electromagnetic wave, bringing much change in human life. High frequency electronics technology has provided radio, television, cellular phone, and so on. From optics and photonics, optical communication, LED lamp, endoscope, etc. have been produced'--
Includes bibliographical references and index.
Keywords: Terahertz technology; Electronic circuits; Very high speed integrated circuits